Genotype-phenotype association and biochemical analyses of glucose-6-phosphate dehydrogenase variants: Implications for the hemolytic risk of using 8-aminoquinolines for radical cure - Sudsumrit, Sirapapha; Chamchoy, Kamonwan; Songdej, Duantida; Adisakwattana, Poom; Krudsood, Srivicha; Adams, Emily R.; Imwong, Mallika; Leartsakulpanich, Ubolsree; Boonyuen, Usa (Frontiers in Pharmacology, 2022)
Background: Plasmodium vivax remains the malaria species posing a major threat to human health worldwide owing to its relapse mechanism. Currently, the only drugs of choice for radical cure are the 8-aminoquinolines (primaquine and tafenoquine), which are capable of killing hypnozoites and thus preventing P. vivax relapse. However, the therapeutic use of primaquine and tafenoquine is restricted because these drugs can cause hemolysis in individuals with glucose-6-phosphate dehydrogenase (G6PD) deficiency. This study aimed to assess and understand the hemolytic risk of using 8-aminoquinolines for radical treatment in a malaria endemic area of Thailand. Methods: The prevalence of G6PD deficiency was determined using a quantitative test in 1,125 individuals. Multiplexed high resolution melting (HRM) assays were developed and applied to detect 12 G6PD mutations. Furthermore, biochemical and structural characterization of G6PD variants was carried out to understand the molecular basis of enzyme deficiency. Results: The prevalence of G6PD deficiency was 6.76% (76/1,125), as assessed by a phenotypic test. Multiplexed HRM assays revealed G6PD Mahidol in 15.04% (77/512) of males and 28.55% (174/613) of females, as well as G6PD Aures in one female. G6PD activity above the 30% cut-off was detected in those carrying G6PD Mahidol, even in hemizygous male individuals. Two variants, G6PD Murcia Oristano and G6PD Songklanagarind + Viangchan, were identified for the first time in Thailand. Biochemical characterization revealed that structural instability is the primary cause of enzyme deficiency in G6PD Aures, G6PD Murcia Oristano, G6PD Songklanagarind + Viangchan, and G6PD Chinese 4 + Viangchan, with double G6PD mutations causing more severe enzyme deficiency. Conclusions: In western Thailand, up to 22% of people may be ineligible for radical cure. Routine qualitative tests may be insufficient for G6PD testing, so quantitative tests should be implemented. G6PD genotyping should also be used to confirm G6PD status, especially in female individuals suspected of having G6PD deficiency. People with double G6PD mutations are more likely to have hemolysis than are those with single G6PD mutations because the double mutations significantly reduce the catalytic activity as well as the structural stability of the protein.